A model of televised election discussion - Isotalus, Pekka (Javnost (Ljubljana), 2006)
The paper describes a model developed for televised election discussion. The aim is to combine the elements of communication, culture and the political situation into a single model. Further, the ways in which these elements influence the nature of political discussion is considered. The main argument is that in the multi-party system of Finland the televised election discussionis indeed a discussion, not a debate. The basic elements of interaction are not attacks and defences as in a debate but rather expressions of agreement or disagreement. The other principal elements are political memory and discourses oriented to the past, future, or present situations.
Keywords: Finska; mölkky; election; volitve; predvolilna kampanja; politična kultura; kandidati; komuniciranje; communication; politične komunikacije; politični marketing; odnosi z javnostmi